Endoscopic retrograde cholangiopancreatography services in Sudan during wartime: Innovations in crisis - Abdelmounem Abdo; Salah Dafalla; Mohammed Bushra; Rodwan Mustafa; Reem Hamad; Ahmed Rafei; Mohamed Jaafer; Rawan Bidab; Waleed Gamus Ojan; Mohammed Ganim; Hala Abdalla (Endoscopy International Open)
​Endoscopic retrograde cholangiopancreatography (ERCP) services in Africa have expanded in recent years, aiming to enhance healthcare infrastructure. ERCP, combining endoscopy and fluoroscopy, diagnoses and treats biliary and pancreatic ductal system conditions. Expanding these services addresses healthcare access disparities between urban and rural populations. ERCP services are well-established primarily in South Africa and Egypt. Countries like Nigeria, Uganda, Rwanda, Ethiopia, and Kenya have sustained ERCP services over the past 5 years. This paper examines the need to expand ERCP services as a step toward health equity in Africa.In Sudan, ERCP services began in 1982 at Soba University Hospital, followed by Ibnsina Specialized Hospital. Before the conflict, only seven centers in Khartoum offered ERCP services. The war that started in April 2023 severely disrupted healthcare services, including ERCP. The National Center for Gastrointestinal and Liver Diseases relocated to Madani City in June 2023, resuming ERCP services by July. By December 2023, 375 procedures were performed. Following further conflict, services moved to Kassala City, where 420 ERCP cases were completed between March and December 2024.​Innovative solutions addressed challenges such as equipment compatibility and accessory availability. A fluoroscopy machine was adapted from a non-functional urology lithotripsy system, and locally designed tables improved procedural efficiency. Development of a local scoring system for trainee assessment after 50 supervised procedures aims to establish a sustainable ERCP fellowship program, addressing the shortage of specialists. These efforts highlight resilience and innovation in delivering ERCP services during conflict.